IMPROVING ENGLISH LEARNING BY USING INTERACTIVE VIDEO AT SMP SATAP PEMATANG JERING - Devi Arisanti; Eza Tri Yandi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
Classroom Action Research on Improving student learning outcomes through the use of Interactive Video is one of the media that helps improve English language learning by introducing students to various expressions in students' daily lives through listening skills for grade VII junior high school students. This research can create an active and independent learning atmosphere. In addition, the Interactive Video introduces students to everyday expressions in English, such as greetings, goodbyes, introducing yourself, introducing others, thank you, and apologizing. The development of Interactive Video designed by using the Classroom Action research design model. then the researcher refers to the process of implementing Classroom Action Research which includes steps including: preparing an action plan, implementing action, observing, and reflecting. Based on the results of the Cycle I evaluation, student learning outcomes were obtained with a class average of 63.6. Then from the evaluation results of Cycle II obtained student learning outcomes with a class average, namely 73. From the results of the study, it can be concluded that the application of learning by using Interactive Video Media can improve student learning outcomes in English subjects in class VII SMPN Satap Pematang Jering. This can also be seen from the results of observations of learning implementation showing an increase in activities at the good and excellent levels from the first cycle to the second cycle.